Pelatihan Inovasi Kewirausahaan Sosial Dalam Produksi Sapu Uyun Berkelanjutan Di Desa Gunasari - Handani, Sari Sri; Mustika, Dena; Haryani, Yunita; Untari, Dewi (Empowerment: Jurnal Pengabdian Masyarakat, 2024)
Gunasari Village in Sumedang Regency has a rich and unique tradition of making Uyun Brooms, but this tradition is threatened with extinction due to modernization and globalization. The use of plastic materials in the production of Uyun Brooms is increasing, while the interest of the younger generation in continuing this skill is decreasing. To overcome this problem, the Social Entrepreneurship Innovation Training program in Sustainable Uyun Broom Production was designed with the aim of returning production methods to the use of natural materials, improving social entrepreneurship skills, and developing sustainable production models that support economic and environmental prosperity. This program will be implemented through several stages, preparation, namely by meeting participants and preparing training modules, implementing intensive training which includes theory and practice, mentoring by mentors through field visits, implementing demonstration plots as a solidification of sustainable production techniques, as well as consultation and social engineering to increase participation. public. Evaluation and reporting will be carried out to assess program achievements. The targeted outputs are Broom Uyun products that use entirely natural ingredients, increasing business management skills and sustainable production among craftsmen, sustainable social entrepreneurship models, effective marketing strategies, and preserving the tradition of making Broom Uyun.